EFEKTIVITAS PENYELENGGARAAN PEMERINTAHAN KAMPUNG DI DISTRIK SILIMO KABUPATEN YAHUKIMO PROVINSI PAPUA - MATUAN, MUSA; KIYAI, BURHANUDDIN; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2015)
ABSTRACTThis study departs from the phenomenon that the villages in the district governance Silimoindicated Yahukimo Papua Province has not been effective . This condition seems to be related to severalfactors inhibiting . Thus , this study aims to : ( 1 ) To determine the effectiveness of village governance ;and ( 2 ) . To determine the factors inhibiting the achievement of effective governance at the village SilimoDistrict Yahukimo .This study used a qualitative approach to the application of descriptive methods . Data andinformation gathered through interviews with 16 informants techniques , and equipped with observationand documentation , then analyzed by applying descriptive analysis techniques .Based on the analysis of data , it is known that : Implementation of the village administration .Particularly in Silimo District Yahukimo generally not effective . This condition can be seen from thereality of the interview in which the criteria for effectiveness penyelnggaraan village administration hasnot been implemented to the maximum .Thus , it can be concluded that there is some obstacle , namely : low accessibility factors , quantityand quality of human resources village government officials are inadequate , infrastructure andgovernment facilities were inadequate , and still strong patriarchal values that characterize the activity ofthe community , especially government officials village that gave birth to the paternalistic culture asinhibitors of achieving effectiveness village governanceTherefore , it is suggested that regional governments need to reform Yahukimo in several sectors , amongothers : land transportation network , infrastructure , equipment , facilities and budget supporting thedelivery of village governance , improving the quality and quantity of resources and village governmentofficials to build a culture system oriented achievement through religious guidance .Keywords : Effectiveness , Government , Village